2006
DOI: 10.1210/jc.2005-1653
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations of Resistin, Coronary Heart Disease, and Insulin Resistance

Abstract: Resistin is not independently associated with CHD. Resistin is elevated in survivors of myocardial infarction; however, this reflects a novel association of raised resistin with diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 33 publications
(40 reference statements)
2
72
1
11
Order By: Relevance
“…A recent study (27) did not find an association between resistin levels and cardiovascular events in Korean diabetic patients, and Pilz et al (28) related resistin levels to inflammatory processes and renal function but not to the incidence of some cardiovascular diseases. In contrast, several other studies (29,30) found that resistin levels are higher in different cardiovascular conditions. More important, the same Pilz et al (28) found an increase in mortality in hyperresistinemic patients, and Lubos et al (31) demonstrated that resistin levels predict cardiovascular mortality in patients with coronary artery disease.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent study (27) did not find an association between resistin levels and cardiovascular events in Korean diabetic patients, and Pilz et al (28) related resistin levels to inflammatory processes and renal function but not to the incidence of some cardiovascular diseases. In contrast, several other studies (29,30) found that resistin levels are higher in different cardiovascular conditions. More important, the same Pilz et al (28) found an increase in mortality in hyperresistinemic patients, and Lubos et al (31) demonstrated that resistin levels predict cardiovascular mortality in patients with coronary artery disease.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast to the rodent, where resistin appears to be important in modulating hepatic insulin sensitivity (24,25), the contribution of resistin to insulin resistance in human subjects appears to be relatively minor. While a few studies have reported a weak positive association between insulin resistance and resistin levels (14,26,27), the majority of studies have not (23,28 -33). Resistin levels in human subjects are thought to correlate more closely with inflammation than with insulin resistance (28,30,34).…”
Section: The Contribution Of Adipose Tissue To Adipokine Levelsmentioning
confidence: 99%
“…Supporting this theory, adults with MetS tend to have higher resistin levels than their healthy counterparts. 29 However, the correlation between insulin resistance and plasma resistin in adult humans remains controversial, supported by some studies 25,[35][36][37] and not in others, 4,21,34,38,39 and this therefore weakens the relation between resistin and MetS.…”
Section: Introductionmentioning
confidence: 99%